Patient satisfaction in inpatient psychiatric treatment compared with inpatient equivalent home treatment in Germany: an in-depth qualitative study - Adam, Nele; Neumann, Melanie; Edelhäuser, Friedrich (Frontiers in Health Services, 2023)
Background Inpatient treatment (IT) is the predominant form of psychiatric care in Germany and worldwide, whereby forms of psychiatric treatment have mainly evolved in the direction of home services. Inpatient equivalent home treatment (IEHT) is a new and additional pillar of psychiatric acute care provision legally embedded since 2018 in Germany. Objective The aim of this study was to conduct an in-depth exploration as little qualitative research has been performed so far in Germany to examine possible differences in patient satisfaction with IT compared with IEHT. Methods In the current qualitative study, N = 9 patients of a German hospital providing IT and IEHT were interviewed with the problem-centered interview. Inclusion criteria were IT or IT with subsequent IEHT. The theoretical sampling method was applied to select test persons in the research process. The experiences of the participants during their psychiatric treatment were analyzed using a qualitative content analysis. Results The results of both types of psychiatric treatment refer to different satisfaction factors during the treatment period. The function of fellow patients, the setting of the treatment, the conditions in place, and the relationship to relatives turn out to be pivotal for patient satisfaction. In addition, the quality of the therapy and relationship to caregivers itself can have an impact on patient satisfaction, particularly by shared decision making. During the IEHT, patient satisfaction can be strengthened by the possibility to handle daily tasks, to be close to relatives, while not so close to fellow patients, whereas IT patients are mostly satisfied because of the distance to their everyday life and the closeness to fellow patients. The choice of the form of psychiatric treatment according to the individual needs of the patients seems to be one key driver that can in turn increase patient satisfaction. In addition, a clean and hygienic environment seems to be critical for our respondents as a lack of it is one of the reasons to drop out of treatment. Conclusions Despite its limitations, this hypothesis-generating study is one of the first investigating German IEHT in comparison with IT in an in-depth qualitative approach contributing to a patient-oriented and cost-effective psychiatric treatment. Although hospitals are highly complex organizations and therefore not directly comparable, other German and international providers of IEHT may derive several generic success factors from this study for the development and improvement of patient satisfaction.